Occupational Stress in Nurses at Hajj Hospital UIN Syarif Hidayatullah Jakarta: The Role of Conflict with Doctor and Death Exposure - Erika Agustianti; Triana Srisantyorini; Munaya Fauziyah; Dewi Purnamawati; Siti Nur Aisyah Djauharoh (The Avicenna Medical Journal, 2024)
Background: In the demanding healthcare environment, both nurses and doctors are at high risk of experiencing stress, with nurses being particularly vulnerable to various psychosocial hazards. This risk also applies to nurses at Hajj Hospital UIN Syarif Hidayatullah Jakarta, especially following organizational changes and nurse rationalization implemented since 2024. The aim is to identify contributing factors to occupational stress and inform interventions to improve nurses' well-being and the quality of healthcare services. Methods: A cross-sectional analytical study was conducted involving all 96 nurses at Hajj Hospital UIN Syarif Hidayatullah Jakarta. Data was collected using Expanded Nursing Stress Scale (ENSS) to asses hazard psychosocial and Workplace Stress Scale (WSS) to evaluate occupational stress levels through a Google Form. The study examined the association between conflict with doctors and lack of experience with End of life (independent variables) and the nurses' reported stress levels (dependent variable). Results: The study revealed a significant association between conflict with doctors and occupational stress (p=0.000), with nurses experiencing conflict being 6.13 times more likely to experience occupational stress (95% CI: 2.337-16.106). A significant relationship was also found between limited experience with End of life and occupational stress (p=0.017), with nurses having limited experience facing a 2.07-fold increased risk of occupational stress (95% CI: 1.188-3.612). Conclusion: The occupational stress experienced by nurses at Hajj Hospital UIN Syarif Hidayatullah Jakarta is significantly related to conflict with doctors and limited experience in managing End of life situations.